Cultivating spiritual resources for improving undergraduate students’ mental health - Irwan Nuryana Kurniawan (Jurnal Aplikasi IPTEK Indonesia, 2018)
The increasing number of students coming to the university’s guidance and counseling unit demonstrates the need for more serious and systemic efforts to deal with students’ mental health. Previous studies have shown that religion has significant contribution to the human mental health and psychological well-being. This study specifically examined the role of one of the spiritual resources that get emphasis in Islamic teachings that is “Tawakal toward Allah Subhanahu wa Ta’ala” to the undergraduate students’ mental health. To test the research hypothesis that asserted there is a positive relationship between surrender to God and social-emotional health, current study uses correlational design. The study involved 57 undergraduate students of the statistic class at Psychology Department of Islamic University of Indonesia, Yogyakarta and Surrender to God Scale (Wong-McDonald & Gorsuch, 2000)and Social-Emotional Health Survey (Furlong, You, Shishim, & Dowdy, 2017) were administered to them. When social desirability on the relationship between surrender to God and social-emotional health was controlled, partial correlation r (56) = .510, p = .001was found.The result suggests that there was a significant and strongly positive association between surrender to God and students’ social-emotional health when controlling social desirability scores.